Aplikasi Toko Online dengan Penerapan Sistem Payment Gateway untuk Transaksi Pembayaran Berbasis Web - Habibullah, Yusril; Sudianto, Aris; Permana, Bq. Andriska Candra (Jurnal PRINTER: Jurnal Pengembangan Rekayasa Informatika dan Komputer, 2023)
The development of information technology and the internet has changed consumers’ behavior in buying and selling transactions. This causes the online buying and selling business to grow rapidly. We can find this online buying and selling activity in various media such as social media platforms and online shop websites. However, most of the payment systems are though bank transfer system and then confirmation of proof of payment, which is arguably not safe and efficient. This is impractical and vulnerable from a security point of view, especially if payments are made online. Therefore, this study aims to design a web-based online store application by implementing a payment gateway system for safer and more efficient payment transactions. The method used in this study is the waterfall method with the stages of needs analysis, design, implementation, testing and maintenance. The result of this study is the design of an online store application that has been equipped with online payment services using the Midtrans payment gateway. This system provides transaction security for customers and can make it easier for buyers to make online payments when placing orders for products because with the payment gateway system, there are more choices of payment methods, including credit cards, bank transfers, electronic wallets (GoPay), or Indomaret and Alfamart, and many more. In addition, this research is also expected to contribute to online buying and selling businesses, especially the development of better online shop applications and provide inspiration for the public to start innovate in promoting their business products.